Seleno-Amino Acids in Vegetables: A Review of Their Forms and Metabolism - Hu, Jiangtao; Wang, Zheng; Zhang, Li; Peng, Jie; Huang, Tao; Yang, Xiao; Jeong, Byoung Ryong; Yang, Qichang (Frontiers in Plant Science, 2022)
Seleno-amino acids are safe, health-promoting compounds for humans. Numerous studies have focused on the forms and metabolism of seleno-amino acids in vegetables. Based on research progress on seleno-amino acids, we provide insights into the production of selenium-enriched vegetables with high seleno-amino acids contents. To ensure safe and effective intake of selenium, several issues need to be addressed, including 1) how to improve the accumulation of seleno-amino acids, and 2) how to control the total selenium and seleno-amino acids contents in vegetables. The combined use of plant factories with artificial lighting and multiple analytical technologies may help to resolve these issues. Moreover, we propose a precise control of selenium content production system, which has the potential to produce vegetables with specified amounts of selenium and high proportions of seleno-amino acids.